Implementation of Simple Clean Water Filtration Technology for Communities Along the Deli River in Medan - Evri Ekadiansyah; Muhammad Aldo; Muhammad Ranu Al Habib; Abdul Fatah Hassanudin (Outline Journal of Community Development, 2025)
The availability of clean water is a basic need that is vital for public health and well-being. However, communities living along the Deli Riverbanks in Medan face serious air quality issues due to household and industrial waste pollution. This Community Service (PKM) activity aims to implement a simple clean water filtration technology that can be built with local materials, is easy to operate, and is affordable for lowland communities. The methods used include an initial air quality survey, training in building the filtration system, installation of units in residents' homes, and technical and social evaluations. The filtration system uses layered media consisting of palm fiber, gravel, fine sand, and activated charcoal in a plastic drum container. Laboratory tests showed that this system effectively reduced air turbidity from 78 NTU to 4 NTU and eliminated Escherichia coli contamination to 0 MPN/100 ml, approaching the national clean water quality standard. In addition to the technical aspects, this activity also had an impact on increasing community awareness of the importance of clean water and healthy lifestyles. The community satisfaction level with the quality of the filtered water reached over 90%, and the majority expressed a desire to replicate the system independently. This activity demonstrates that locally based appropriate technology can be an effective solution in addressing clean water problems in poor urban areas, as well as strengthening community capacity and independence in managing water resources sustainably.